Предмет: Математика,
автор: Mila84763
3(y+1)=6(1-y)+6
Даю 22 бали
Ответы
Автор ответа:
0
3(у + 1) = 6(1 - у) + 6
3у + 3 = 6 - 6у + 6
3у + 6у = 6 + 6 - 3
9у = 9
у = 9 : 9
у = 1
Проверка: 3(1 + 1) = 6(1 - 1) + 6
3 + 3 = 6 - 6 + 6
6 = 6
3у + 3 = 6 - 6у + 6
3у + 6у = 6 + 6 - 3
9у = 9
у = 9 : 9
у = 1
Проверка: 3(1 + 1) = 6(1 - 1) + 6
3 + 3 = 6 - 6 + 6
6 = 6
Автор ответа:
0
Дякую
Похожие вопросы
Предмет: Биология,
автор: yanazhidkova08
Предмет: Алгебра,
автор: makspetrovic52
Предмет: Қазақ тiлi,
автор: Popajwkjdbwjba030310
Предмет: Математика,
автор: 1976020319760203
Предмет: Химия,
автор: abror888